AN ANALYSIS ON THE PREPAREDNESS FOR IMPLEMENTING THE MINIMAL STANDARDS FOR SERVICE IN THE HEALTH FIELD AT DEPOK CITY IN 2017 - Zakiah, Zakiah; Junadi, Purnawan (Journal of Indonesian Health Policy and Administration, 2019)
Health is one of the fundamental rights for every person, therefore it must be provided by the government. To guarantee the quality and type of health services, the Minimal Standards for Services (SPM) must be established. This includes the SPM for the productive age healthcare services (SPM BKUP). This type of healthcare is important since it covers about 60-70% of the current population. In this research, we analyzed the discrepancy between the reality and the ideal in the implementation of the SPM BKUP qualitatively through in-depth interviews, focus group discusions, and studying the related documents. We discovered that in Depok City 10 of the 13 indicators for implementation were incomplete. These were the Noncommunicable diseases (NCDs) risk factor conseling, technical trainings for the screening officer and web-based surveillance, NCDs integrated services, recording and reporting, monitoring and evaluation, communication, the attitude of the implementer, manpower, facilities, and funding. And that the other three indicators, incentives for the implementers that reached the target, standard operational procedures for the implementation of the SPM BKUP, and a specialized team for the implementation. Therefore, Depok City was only minimally prepared to implement the SPM.